Peers Teenagers Healthy Prevent Drug Abuse on Teenagers in School - Roma Tao Toba MR; Elly Nurachmah; Astuti Yuni Nursasi; Tris Eryando; Arman Harahap (Budapest International Research and Critics University, 2021)
Adolescence is a period of transition from children to adult. The young undergo metamorphosis physical impact for the progress of the psychological result in adolescents at risk of experiencing health problems. A problem that is often experienced in adolescents between the other Drug abuse. Research objectives to get an overview of the effectiveness of Peer Teenagers Healthy (TEBARS) in the prevention of Drug abuse in adolescents in school, using a quasi-experiment, the sample obtained by random. The results illustrate Peers Teenagers Healthy is quite effective in preventing Drug abuse on teenagers in school, lack of knowledge of the average of 28.83 be 27.59, SD 1.558, p=0.000, risky behavior average of 49.23 be 43.32, SD 4.365, p=0.000. The average appearance Peers Teenagers Healthy before the intervention of 5.3 points increased to 7.8 point. The results of this study are expected to be implemented in schools and developed and fostered more to prevent Drug abuse.